Evaluation of organic amendment in corn production in Villaflores, Chiapas, Mexico - Aguilar, Carlos; Aguilar, Franklin; Zapata , Isidro; Aguilar , José; Zamora , Juan (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The use of organic fertilizers contributes to the improvement of the fertility of agricultural soils. The objective was to evaluate three doses of organic fertilizer incorporated into the soil (10, 20 and 30 t.ha-1) and a control, in corn production. The management of the crop was conventional, after the preparation of the soil with agricultural machinery, the doses of compost were incorporated. Planting was manual with a density of 66,500 plants.ha-1. A completely randomized design and three replicates per treatment were used. Data were analyzed with analysis of variance, tests of means, correlation analysis, and economic evaluation. The results indicated that the incorporation of organic fertilizer to the soil benefited the height of the plant and ear, leaf area, stem diameter, number and yield of ears.ha-1. A direct and positive relationship was found between the dose of amendment incorporated into the soil and the production of ears in the milky-dough state. The application of 30 t.ha-1 of organic fertilizer showed the best results for the indicated agronomic variables and presented the best economic benefits.